Fine-tuning the ubiquitin code at DNA double-strand breaks: deubiquitinating enzymes at work - Citterio, Elisabetta (Frontiers in genetics, 2015)
Ubiquitination is a reversible protein modification broadly implicated in cellular functions. Signaling processes mediated by ubiquitin (ub) are crucial for the cellular response to DNA double-strand breaks (DSBs), one of the most dangerous types of DNA lesions. In particular, the DSB response critically relies on active ubiquitination by the RNF8 and RNF168 ub ligases at the chromatin, which is essential for proper DSB signaling and repair. How this pathway is fine-tuned and what the functional consequences are of its deregulation for genome integrity and tissue homeostasis are subject of intense investigation. One important regulatory mechanism is by reversal of substrate ubiquitination through the activity of specific deubiquitinating enzymes (DUBs), as supported by the implication of a growing number of DUBs in DNA damage response processes. Here, we discuss the current knowledge of how ub-mediated signaling at DSBs is controlled by DUBs, with main focus on DUBs targeting histone H2A and on their recent implication in stem cell biology and cancer.